Exploitation as innovation: research ethics and the governance of experimentation in the urban living lab. Issue 12 (2nd December 2021) - Taylor, Linnet
ABSTRACT: As data technologies become the medium of experiment for living labs, they become less a collaboration between citizen and researcher and more a test of how commercial actors can influence the public. Two new practices suggest we should apply research ethics rules: first, that the experimentation taking place does not aim to test technology using people, but to test people using technology; and second, that such experimentation is explicitly designed to understand how the population outside the lab can be influenced and manipulated, and therefore has a political character that research ethics can give us some leverage over.